Optimizing tax administration: A comprehensive analysis of the effect of e-filing tax system on taxpayers’ compliance burden in Tanzania - MILAMO, Rufina Justine; MAGOBE, Mato James (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2024)
Employing partial least squares structural equation modeling (PLS-SEM), the study examines the effects of tax system quality factors on corporate taxpayers’ usage of the e-filing tax system. Additionally, it explores the relationship between e-filing tax system usage and tax compliance burden. The analysis is based on survey data collected from 250 medium and large taxpayers, who were already engaged in online VAT return filing before 2020. The findings reveal that system quality and service quality significantly influence extent of taxpayers’ usage of the e-filing tax system, leading to a subsequent reduction in the tax compliance burden. The study contributes to academic knowledge by applying a modified version of DeLone and McLean’s Information System Success model to assess the success of e-filing in an environment characterised by mandatory adoption. The practical implications highlight the necessity for tax authorities to implement measures aimed at improving the user-friendliness and service-oriented functionalities of the e-filing tax system. This research holds significance as it provides valuable insights into enhancing the effectiveness of the e-filing tax system within a mandatory adoption context, offering guidance for policymakers and tax authorities to improve tax compliance and overall system performance.